Hazrat nizam ud din auliya(R.A) - Aijaz Begam Zakir (Pakistan, 2005)
Hazrat Nizam-ud-Din Auliya (R.A) highlights the life and teachings of the revered Sufi saint, known for his message of love, humanity, and devotion to God.